2008
DOI: 10.1007/s10980-008-9292-x
|View full text |Cite
|
Sign up to set email alerts
|

Pond density as a determinant of aquatic species richness in an urban landscape

Abstract: Social cues, such as eye gaze and pointing fingers, can increase the prioritisation of specific locations for cognitive processing. A previous study using a manual reaching task showed that, although both gaze and pointing cues altered target prioritisation (reaction times [RTs]), only pointing cues affected action execution (trajectory deviations). These differential effects of gaze and pointing cues on action execution could be because the gaze cue was conveyed through a disembodied head; hence, the model la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
123
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 12 publications
12
123
2
1
Order By: Relevance
“…An average of 28 and a total of 119 aquatic macroinvertebrate taxa were recorded from 37 ponds in the town of Halton, UK, however, this was lower than the wider landscape in the north west of England (Gledhill et al, 2008). The same study indicated that invertebrate biodiversity was higher in ponds in new town developments, where there was a higher density of ponds, than urban ponds in established, old urban areas (Gledhill et al, 2008). Common macroinvertebrate species can colonize even the most degraded urban ponds (Wood et al, 2003).…”
Section: Urban Pondsmentioning
confidence: 89%
See 4 more Smart Citations
“…An average of 28 and a total of 119 aquatic macroinvertebrate taxa were recorded from 37 ponds in the town of Halton, UK, however, this was lower than the wider landscape in the north west of England (Gledhill et al, 2008). The same study indicated that invertebrate biodiversity was higher in ponds in new town developments, where there was a higher density of ponds, than urban ponds in established, old urban areas (Gledhill et al, 2008). Common macroinvertebrate species can colonize even the most degraded urban ponds (Wood et al, 2003).…”
Section: Urban Pondsmentioning
confidence: 89%
“…Previous research has highlighted urban ponds' considerable contribution to biodiversity (Gledhill et al, 2008;Hassall, 2014;Hassall and Anderson, 2015) whilst other studies have suggested that urban ponds are often ecologically poor and currently of little value to aquatic conservation (Noble and Hassall, 2014). …”
Section: Pond Habitatsmentioning
confidence: 99%
See 3 more Smart Citations